Metabolic Reprogramming of Non-Hodgkin's B-Cell Lymphomas and Potential Therapeutic Strategies - Ricci, Jean-Ehrland; Chiche, Johanna (Frontiers in Oncology, 2018)
Metabolism is a wide and general term that refers to any intracellular pathways the cell utilizes in order to satisfy its energetic demand and to support cell viability and/or division. Along with phenotypic changes, all mammalian cells including immune cells modulate their metabolic program in order to reach their effector functions. Exacerbated metabolism and metabolic flexibility are also hallmarks of tumor initiation and of tumor cell progression in face with a complex tumor microenvironment. Metabolic reprogramming is mainly directed by the serine/threonine kinase mTOR (mammalian target of rapamycin). mTOR exists in two structurally and functionally distinct complexes, mTORC1 and mTORC2 that coordinate environmental signals and metabolic/anabolic pathways to provide macromolecules and energy needed for survival and growth. Activation of mTORC1 is required during development, differentiation and activation of immune cells. Aberrant and persistent activation of mTORC1 is often observed in malignant B cells such as Non-Hodgkin’s (NH) B-cell lymphomas. Here, we review recent insights on cell metabolism and of basic mechanisms of mTORC1 regulation and metabolic functions. We highlight the distinct mechanisms driving mTORC1 activation in the three most-common types of NH B-cell lymphomas (Diffuse Large B Cell Lymphomas, Follicular Lymphomas and Mantle Cell Lymphomas), for which the first generation of mTORC1 inhibitors (rapalogues) have been extensively evaluated in preclinical and clinical settings. Finally, we discuss the reasons for limited clinical success of this therapy and focus on potential therapeutic strategies targeting metabolic pathways, upstream and downstream of mTORC1, that can be combined to rapalogues in order to improve patient’s outcome.